Impact of society and national guidelines on patient selection for lung cancer surgery in the United Kingdom. (29th June 2022) - Pons, Aina; De Sousa, Paulo; Proli, Chiara; Booth, Sarah A; Palmares, Abigail; Leung, Maria; Alshammari, Abdullah; Vlastos, Dimitrios; Raubenheimer, Hilgardt; Devbhandari, Mohan; Patel, Anant; Lim, Eric
Abstract: OBJECTIVES: We sought to evaluate the impact of different national clinical guidelines (with consistent and conflicting recommendations) on clinician's practice in the UK. METHODS: In this cohort study, we analysed data from National Lung Cancer Audit comprising all patients diagnosed with lung cancer between 2008 and 2013 within England and Wales for consistent (British Thoracic Society and National Institute of Clinical Excellence) recommendations for lower/more permissive lung function but opposing stage (N2) selection parameters for surgery. RESULTS: From 2008 to 2013, data from 167 192 patients with primary lung cancers were included. The proportion of patients undergoing surgery for lung cancer increased from 9.5% to 20.5% in 2013 ( P  < 0.001) as the number of general thoracic surgeons in the UK increased from 40 to 81 in the corresponding timeframe. Mean forced expiratory volume in 1 s of surgical patients increased from 76% (22) to 81% (22) in 2013 ( P  < 0.001). Of the patients undergoing surgery, the proportion of patients with N2 disease across the 6-year interval was broadly consistent between 8% and 11% without any evidence of trend ( P  = 0.125). CONCLUSIONS: Within 3 years of new clinical guideline recommendations, we did not observe any overall change suggesting greater selection for surgery on lower levels of lung function. When presented with conflicting recommendation, no observable change in selection was noted on surgery for N2 disease. The observed increase in surgical resection rates is more likely due to greater access to surgery (by increasing number of surgeons) rather than any impact of guideline recommendations. Abstract : Whilst surgery is widely considered to be the standard of care for the treatment of early-stage lung cancer, considerable variation exists in the threshold of recommendation by clinicians and acceptance by patients [1].